2006
DOI: 10.1073/pnas.0601296103
|View full text |Cite
|
Sign up to set email alerts
|

High expression of a cytokeratin-associated protein in many cancers

Abstract: We have described previously a cDNA library made from membrane-bound polysomal mRNA prepared from breast and prostate cancer cell lines. The library is highly enriched for cDNAs encoding membrane proteins, secreted proteins, and cytokeratins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 16 publications
0
33
2
Order By: Relevance
“…It was recently shown that a BK channel auxiliary protein (LRRC26) is responsible for the hyperpolarized activation of the BK channels in these prostate cancer cells (Yan and Aldrich, 2010). In addition to the prostate, LRRC26 is also highly expressed in normal salivary glands and at low levels in colon, pancreas, and intestine (Egland et al, 2006). In addition, the LRRC26 protein was found in human parotid exosomes along with TMEM16A and NKCC1, proteins that are primarily, if not exclusively, expressed in acinar cells (Gonzalez-Begne et al, 2009).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was recently shown that a BK channel auxiliary protein (LRRC26) is responsible for the hyperpolarized activation of the BK channels in these prostate cancer cells (Yan and Aldrich, 2010). In addition to the prostate, LRRC26 is also highly expressed in normal salivary glands and at low levels in colon, pancreas, and intestine (Egland et al, 2006). In addition, the LRRC26 protein was found in human parotid exosomes along with TMEM16A and NKCC1, proteins that are primarily, if not exclusively, expressed in acinar cells (Gonzalez-Begne et al, 2009).…”
Section: Resultsmentioning
confidence: 98%
“…However, MTX was not entirely without effect as it produced a 2-fold increase in the speed of parotid BK channel activation. We showed that the limited action of MTX on the voltage dependence of BK channel activation in parotid cells was probably attributed to the existence of a BK channel accessory protein, LRRC26, which is expressed in salivary glands, including parotid (Egland et al, 2006;Gonzalez-Begne et al, 2009). Coexpression of parSlo with LRRC26 produced chan- molpharm.aspetjournals.org nels that mimicked many of the properties of those in the native cells, including 1) a hyperpolarized activation range, 2) resistance to MTX modification of steady-state activation, and 3) a speeding of gating kinetics by MTX.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that membrane proteins may bind directly to IFs, which may be the case for polycystin-1 [90], a protein that, in addition to its well-known apical cilium localization, also concentrates around desmosomes [91]. Other examples are the interaction between aquaporin and filensin [92] and a 334-aa cancerassociated protein with the structure of a membrane protein that colocalizes with IFs [93]. It is also conceivable, that IFs may serve as scaffolds for extrinsic membrane proteins that, in turn interact with membrane proteins.…”
Section: Role Of Keratin Ifs In Epithelial Polarizationmentioning
confidence: 99%
“…Before its recognition as a likely BK regulatory subunit, message and protein for human LRRC26 was initially observed in a variety of cancer cell lines and human cancer samples (CAPC) (16). CAPC was found to inhibit tumor cell proliferation and tumor growth by regulating NF-κB and its target genes (20).…”
Section: Potential Roles Of Lrrc26-containing Bk Channels In Tumor Grmentioning
confidence: 99%
“…LRRC26 was originally identified in several cancer cell lines and termed cytokeratin-associated protein in cancers (CAPC) (16). Subsequently it was shown to be a regulatory subunit of BK channels (12), later defined as γ1 (14).…”
mentioning
confidence: 99%